Mitka's secret : a true story of child slavery and surviving the Holocaust - Brallier, Steven W.; Lohr, Joel N.; Beck, Lynn G. (William. B. Eerdmans Publishing Company, 2021)
"The remarkable life story of Mitka Kalinski, who, while still a child, survived the Holocaust and seven years of enslavement to a Nazi officer, then began a new life in the United States and revealed his secret past decades later"--